Theoretical and experimental study of the vibrational spectra of (para)symplesite and hörnesite - Makreski, Petre; Stefov, Stefan; Pejov, Ljupčo; Jovanovski, Gligor (My University, 2015)
Arsenate water-bearing minerals, hörnesite (Alšar, Macedonia) and symplesite (Laubach, Germany), were studied by vibrational (IR and Raman) spectroscopy and X-ray powder diffraction. The observed vibrational spectra in both the high (1100-600 cm(-1)) and low (600-450 cm(-1)) wavenumber regions of AsO4 and H2O vibrations could be used to discriminate the two studied minerals. Spectral differences are especially pronounced in the bending and stretching regions of the H2O vibrations in the IR spectra. The observed bands in IR and Raman spectra were tentatively assigned. To support the assignment, IR spectra were theoretically simulated. These calculations were performed using the crystal structure of parasymplesite (no structural information of symplesite has been published so far) and hörnesite using a 3D periodic plane-wave pseudopotential density functional theory approach applying various combinations of exchange-correlation functionals. In this article, we report on the first experimental study of the vibrational spectra of the very rare symplesite mineral.